2016
DOI: 10.5658/wood.2016.44.6.842
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phenol Formaldehyde Impregnation on The Physical and Mechanical Properties of Soft-Inner Part of Oil Palm Trunk

Abstract: The objective of this study was to improve physical and mechanical properties of soft-inner part of oil palm trunk (S-OPT) after impregnation with phenol formaldehyde (PF) resin and densification by close system compression (CSC) method. Effect of different methods of PF resin impregnation (i.e., no vacuum-pressure, vacuum, and vacuum-pressure) was evaluated. The results showed that PF resin impregnation and CSC significantly improved the physical and mechanical properties of S-OPT up to: (1) 176% in density; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…It is thought that the comparatively high initial density (0.63) of teak wood in this experiment partially affects the low penetreation rate. In earlier reports, the low initial specific gravity values in other species (0.5>) such as oil palm trunk (Sumardi et al 1999;Aini et al 1999;Hartono et al 2016), sesenduk and jelutong (Adawiah et al 2012;Ashaari et al 2015) showed drastic increases in density levels. Another possibility is the unsuitable molecular weight of PF in this experiment (4000 Mn).…”
Section: Specific Gravity and Moisture Contentmentioning
confidence: 90%
See 1 more Smart Citation
“…It is thought that the comparatively high initial density (0.63) of teak wood in this experiment partially affects the low penetreation rate. In earlier reports, the low initial specific gravity values in other species (0.5>) such as oil palm trunk (Sumardi et al 1999;Aini et al 1999;Hartono et al 2016), sesenduk and jelutong (Adawiah et al 2012;Ashaari et al 2015) showed drastic increases in density levels. Another possibility is the unsuitable molecular weight of PF in this experiment (4000 Mn).…”
Section: Specific Gravity and Moisture Contentmentioning
confidence: 90%
“…Furthermore, phenol formaldehyde has several advantages in improving wood quality (Way et al 2011;Ashaari et al2015;Ang et al 2014;Franke et al 2017). Phenol formaldehyde resin impregnation and compression at high pressures significantly increase the strength of wood, especially flexural resistance, dimensional stability, and biological durability (Shams and Yano 2008;Nabil et al 2016;Hartono et al 2016). Therefore, this paper discussed on the improvement the physical properties of young teak wood by compregnation treatment using phenol formaldehyde.…”
Section: Introductionmentioning
confidence: 98%
“…Penelitian-penelitian mengenai impregnasi perekat ke dalam kayu telah banyak dilakukan (Furuno et al 2004, Shams et al 2006, Bakar et al 2013, Hartono et al 2016, namun masih terbatas pada penggunakan perekat sintesis seperti formaldehida, sedangkan penggunaan perekat alami seperti asam sitrat belum pernah dilakukan. Metode pre-kompresi telah dikembangkan dengan tujuan untuk meningkatkan daya serap larutan ke dalam kayu, terutama terhadap jenis-jenis kayu yang memiliki permeabilitas rendah.…”
Section: Pendahuluanunclassified
“…Therefore, continuous research is needed to modify the sugar palm stems properties so that they can be utilized properly. Some researchers have used palm sugar as raw material for a wood floor or parquet [7]. Other uses are impregnating oil palm stem structure with resins such as formaldehyde phenol [14].…”
Section: Figurementioning
confidence: 99%
“…Some researchers have used palm sugar as raw material for a wood floor or parquet [7]. Other uses are impregnating oil palm stem structure with resins such as formaldehyde phenol [14]. Impregnation will improve the quality of physical, mechanical, and durability of sugar palm stem.…”
Section: Figurementioning
confidence: 99%